CALLUS INDUCTION AND PLANT REGENERATION FROM MATURE SEEDS OF SIBERIAN WILDRYE GRASS (ELYMUS SIBIRICUS L.) - K. W. Lee; O. Chinzorig; G. J. Choi; K. Y. Kim; H. C. Ji; H. S. Park; S. H. Lee (Journal of Animal and Plant Sciences, 2012)
In order to optimize tissue culture conditions of Siberian wildrye grass, the effects of plant growth regulators and various carbon sources on callus induction and plant regeneration was investigated with mature seeds. The optimal concentration of 2,4-D for the induction of primary callus from mature seeds was 5 mg/L. The highest embryogenic callus frequency was observed when the mature seed were cultured on MS medium supplemented with 5 mg/L 2,4-D and 0.1 mg/L BA(6-benzyladenine). The highest plant regeneration frequency was observed when callus was transferred to N6 medium supplemented with 1 mg/L 2,4-D and 3 mg/L BA. Regenerated plants were rooted at the highest rate (100%) when transferred onto 1/2 MS medium. Regenerated plants were morphologically uniform with normal growth pattern. A short tissue culture period and regeneration system would be beneficial for molecular breeding of Siberian wildrye grass by the production of transgenic plant.
Keywords: Siberian wildrye grass; Elymus Sibiricus L.; Callus; Plant regeneration; Grassland